EFFECTIVE METHODS FOR ORGANIZING STUDENTS' INDEPENDENT LEARNING SESSIONS (American Journal of Research in Humanities and Social Sciences, 2025)
This article discusses the main conditions for effectively organizing independent learning in the subject of Applied Decorative Arts within the Fine Arts and Engineering Graphics educational program at higher education institutions. Based on the objectives and tasks of the course, the article outlines the stages of developing students' independent learning skills and competencies.